Religious Harmony Among Senior High School Students Multicultural Education Case Study in the Cova-Lima District of East Timor - Soares, Francisco; Sudarsana, I Ketut (Institut Hindu Dharma Negeri Denpasar, 2018)
Harmony is a state where there is mutual understanding, unity, cooperation, peace and friendship among members who live together for a purpose of nation and state. In addition it can also mean that harmony is a state that reflects mutual understanding and agreement among members so as to create peace and harmony. Religious harmony is not the religious teachings blend in the sense of mixing up the religious teachings, but the harmony between different religious faiths. Religious harmony can be realized if there is a tolerance among believers of different faiths. The attitude of tolerance is no other way by controlling yourself in attitude toward others, so that others do not feel harmed or threatened. The attitude of self-control is of course not just coming from one party. This should be done by every believer of different religions.